Produtos naturais como inibidores das proteínas 3CLpro e Spike do SARS-CoV-2: um estudo in silico integrado - Santos, Samuel José Mendes dos (2024)
The COVID-19 pandemic, caused by SARS-CoV-2, brought the world to a standstill and underscored the urgent need for new therapeutic agents capable of inhibiting proteins essential for viral replication and infectivity. In this context, the inhibitory potential of the natural compounds barbatusol, brussonol, and komaroviquinona against the SARS-CoV-2 Mpro and Spike proteins, with a focus on the Omicron BA.2 variant, was investigated using in silico methods, which are crucial for accelerating drug discovery and optimization. Molecular dynamics simulations, molecular docking, and quantum chemistry calculations (QM/MM and DFT) were performed to evaluate the stability and interactions of these compounds with the target proteins. Additionally, ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) studies were conducted to predict the pharmacokinetic properties of the ligands, which are essential for determining the efficacy and safety of new drugs. The importance of these studies lies in the ability to select compounds that are not only effective but also possess a favorable safety profile, minimizing adverse effects. Furthermore, molecular fingerprint analyses using MACCS-166 and ECFP-6 were conducted to characterize the structural similarity with known compounds, aiding in the identification of functional properties and the prediction of pharmacological behaviors. The binding site characterization of the proteins was carried out based on literature and the tools ProBiS, GRaSP, and COACH, which enabled the identification of critical interactions contributing to the efficacy of the compounds. The results indicated that barbatusol, brussonol, and komaroviquinona exhibit binding affinities similar to those of the reference compounds nirmatrelvir and mefloquina, suggesting their potential as antiviral candidates against SARS-CoV-2. ADMET analysis revealed that the natural products studied possess superior pharmacokinetic properties and more favorable toxicity profiles compared to nirmatrelvir, indicating a promising and safer therapeutic potential against COVID-19. It is concluded that the studied compounds are promising drug candidates and may significantly contribute to the development of new antiviral therapies.